After the Null Subject Parameter: Acquisition of the Null-Overt Contrast in Spanish. Issue 2 (3rd April 2022) - Forsythe, Hannah; Greeson, Daniel; Schmitt, Cristina
ABSTRACT: In many so-called canonical null subject languages, null and overt subject pronouns have contrasting referential preferences: null subjects tend to maintain reference to the preceding subject while overt pronominal subjects do not. We propose that children acquire this contrast by initially restricting their attention to 1 st and 2 nd person pronouns, whose reference is simpler to infer compared to 3 rd person pronouns. We provide supporting evidence from spontaneous production and comprehension in Mexico City Spanish, showing that (i) the null/overt contrast is in principle acquirable from exclusively observing the referential preferences of 1 st and 2 nd person subject pronouns in caretaker speech; (ii) children themselves condition subject pronoun expression on pronoun reference in the 1 st and 2 nd persons before doing so in the 3 rd person; and (iii) children use the null/overt contrast in comprehension at a similar age when they begin making this distinction in production.